Moral characteristics of the female characters in the oldest epic songs: A Sociological Analysis of content - Redžić, Saduša F. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The study aims to, in terms of the sociology of morality, analyzes the characters of women in the oldest Serbian epic poems using sociological content analysis. The results indicate the social evaluation of moral characteristics of women, moral actions and personal qualities ascribed to women in the oldest epic poems, moral judgment, sanctions and moral imperatives. Also indirectly indicate the former social status of women and the amount of social power which she possesses. One gets the insight into a part of the mores of a given period of time, sometimes inseparable from the moral community and moral beliefs of folk singers. Female characters should provide and respect life. Highly valued marital fidelity of women, as well as honesty, honor, sacrifice and empathy. To religion and ethnicity poets also subjoin moral value. Respect and obedience to authority are implemented in the moral character of women and form an inseparable part, although they are not accurately moral qualities.
Keywords: content analysis; female; epic poetry; ethics